The estrogen metabolite 17β-dihydroequilenin counteracts interleukin-1α induced expression of inflammatory mediators in human endothelial cells in vitro via NF-κB pathway - Demyanets, Svitlana; Pfaffenberger, Stefan; Kaun, Christoph; Rega, Gersina; Speidl, Walter S.; Kastl, Stefan P.; Weiss, Thomas W.; Hohensinner, Philipp J.; Dietrich, Wolf; Tschugguel, Walter; Bochkov, Valery N.; Awad, Ezzat M.; Maurer, Gerald; Huber, Kurt; Wojta, Johann (Thrombosis and Haemostasis, 2006)
In most studies showing cardio- and vasculoprotective effects of estrogens, 17β-estradiol was used and little information on possible effects of different estrogen metabolites is yet available. We investigated whether particular estrogen metabolites are effective in counteracting inflammatory activation of human endothelium. Human endothelial cells were incubated with 17α-dihydroequilenin, 17β-dihydroequilenin, δ-8,9-dehydroestrone, estrone and 17β-estradiol and stimulated with interleukin (IL)-1α.The expression of IL-6, IL-8 and monocyte chemoattractant protein-1 (MCP-1) was determined. 17β-dihydroequilenin and 17β-estradiol at a concentration of 1µM reduced IL-1α-induced up regulation of IL-6, IL-8 and MCP-1 close to control levels. When both compounds were used in combination an additive effect was observed. 17α-dihydroequilenin and δ-8,9-dehydroestrone showed a similar anti-inflammatory effect only when used at 10µM whereas estrone had no effect. The effect of 17β-dihydroequilenin on IL-1α-induced production of IL-6, IL-8 and MCP-1 was reversed by the estrogen receptor antagonist ICI 182,780. 17β-dihydroequilenin also inhibited IL-1α-induced translocation of p50 and p65 to the nucleus of the cells. We have identified the estrogen metabolite 17β-dihydroequilenin, as an inhibitor of inflammatory activation of human endothelial cells. Characterization of specific estrogens – as shown in our study – could provide the basis for tailored therapies, which might be able to achieve vasoprotection without adverse side effects.
Keywords: Estrogens; endothelial cells; cardiovascular effects; inflammation; cytokines